Impact of herding behavior, risk perception, and financial literacy on student investment decisions in Palembang - Maureen Marcia Marvin; Catharina Clara; Gustiah Elissia (Jurnal Manajemen, 2025)
College students’ investment decisions are often affected by their financial illiteracy and socio behavior in their environment. "This study aims to understand the relationship between herding behavior, risk perception, and financial literacy towards college student investment decisions in Palembang. The exploratory quantitative approach was used in this study and the respondents were student of the Faculty of Business and Accounting (FBA) in Palembang. The sample were 100 respondents with purposive sampling method. For data collection in this research using survey techniques. This analysis uses Smart PLS software 4.0 for Structural Equation Modeling (SEM-PLS). This method includes two parts: the measurement system (outer model) and the structural system (inner model).  The data revealed that financial literacy and risk perception significantly and positively influence students’ investment choices, while herding behavior positively but insignificant influence on students’ investment decisions. Improving understanding of financial concepts can lead to more informed decision-making on investments. This study suggests that future researchers explore other factors not covered here that may influence investment decisions.